Detection, Control and Contamination of Mycotoxins - Cavaliere, Chiara; Laura Capriotti, Anna; Montone, Carmela Maria; Cerrato, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The objective of this collection is to illustrate the most recent research on the development of novel and/or rapid methods for mycotoxin determination, and to propose new strategies for monitoring and/or reducing mycotoxin contamination. Innovative sample preparation techniques or protocols and the possibility of multiclass mycotoxin detection will be very positively considered for possible inclusion in this Special Issue. Both methods based on (bio)sensors and chromatography with various detectors (including mass spectrometry) are welcome. Applications of already published methods on new matrices without any modification will not be accepted. However, extensive studies and monitoring on the spread of contamination through the food production chain could be of interest for this collection.